Споживання в радянському місті у 1920–1930-х роках: між ідеологією та повсякденністю - Скубій, І. (Український історичний збірник, 2017)
У дослідженні розглядаються проблеми споживання в радянському місті у
1920–1930-х роках, які знаходилися на перетині ідеології та повсякденного
життя. Звертається увага на типові риси споживання цього періоду, серед
яких були дефіцит товарів, незадовільний асортимент та якість. Аналізуються
місце держави в його регулюванні та ідеологічному впливі на споживача.
Встановлено, що в умовах становлення тоталітарного ладу нові практики споживання містян стали формою пристосування і протистояння ідеологічним догмам. The article touches upon the issue of consumption in Soviet city in 1920–1930s,
which was connected with ideology and everyday life. Special attention is paid to the
theoretical concept of “consumption”, its understanding by communist ideologists and
authorities as well. It is spoken about the typical features of the consumption practices
of this period, especially shortage of goods, their bad assortment and quality. The
place of state in regulation of the consumption and ideological influence on consumer
is analyzed. It is discovered that mass consumption was directed on the attainment the
collective progress, but not on the satisfying of the individual needs. It is studied the
consumer basket of different social groups of Soviet cities. Much attention is given to
the investigation of the transformation process of the urban space of the early Soviet
society in the investigated period. The article gives detailed analysis of new spaces of
Soviet consumption such as univermags and cooperatives. It was the univermags that
became the “face” of Soviet retail trade and place of satisfying consumer’s demands.
At the same time the Soviet authorities actively used the old spaces of consumption
putting them to the system of state retail trade. It should be noted about those cities as
Kharkiv, Dnipropetrovs’k, and Mykolaiiv that were better satisfied with goods than
others Ukrainian urban centers. It is discovered that during 1920s the consumer was
important figure in the system of retail trade, because of existed competition between
state and private trade. It is stressed that some of the consumption problems from
1920–1930s became the chronic features of Soviet every day life in the next decades.
At the same time Soviet authorities emphasized on temporality of difficulties in
satisfying the people’s needs. The author comes to conclusion that in the conditions of
the formation of totalitarian regime the new consumption practices of town peoples
became the important form of adaptation and confrontation to the ideological dogmas.